YAŞLI HASTALARIN BAKIM VERENLERİNİN BAKIM YÜKÜ İLE İNSOMNİA VE MALNÜTRİSYON ARASINDAKİ İLİŞKİ - Tanrıverdi İ.; Soysal P.; Aydın N. Ö.; Pasin Ö.; Sümbül Şekerci B. (My University, 2025)
Introduction: The elderly population, defined as individuals aged 65 and over, is growing rapidlyworldwide. This demographic shift is leading to an increased burden on caregivers, who areessential in assisting elderly patients. In our study, we aim to determine the burden of caregiversproviding care for elderly patients. Method: Our study was conducted from March 2023 atBezmialem Vakıf University Faculty of Medicine Hospital, focusing on caregivers of hospitalizedpatients aged 65 and over. After collecting personal information, we used the Caregiver BurdenScale (CBS) for caregiver burden, the Mini Nutritional Assessment Test (MNAT) and Healthy EatingAttitude Scale for nutritional status, and the Epworth Sleepiness Scale (ESS) and InsomniaSeverity Index (ISI) for sleep status. For muscle strength, a handgrip dynamometer was applied tothe arm three times, and the maximum result was evaluated. Result: To date, the study hasenrolled 100 volunteer caregivers, comprising 79 females and 21 males, with a mean age of 50.5years. According to the MNAT, the prevalence of undernutrition among participants is 48%. TheESS indicates a daytime excessive sleepiness prevalence of 12%, while the ISI reveals amoderate insomnia rate of 10%. Additionally, the handgrip test shows muscle weakness rates of5% in females and 4% in males. When comparing total scores among participants, afteradjustment for all confounders, a negative correlation was atill observed between CBS and theMNAT, and a positive correlation was found between CBS and the ISI (p<0.05). Conclusion:Caregiver burden is linked to poor nutrition and sleep disturbances. Therefore, the sleep andnutrition status of caregivers should be regularly monitored, and necessary measures should betaken.
Keywords: Sosyal ve Beşeri Bilimler; Sağlık Bilimleri; Social Sciences and Humanities; Health Sciences; Klinik Tıp (Med); Sosyal Bilimler (Soc); Clinical Medicine (Med); Social Sciences (Soc)